Galectin-3 impacts Cryptococcus neoformans infection through direct antifungal effects. Issue 1 (December 2017) - Almeida, Fausto; Wolf, Julie; da Silva, Thiago; DeLeon-Rodriguez, Carlos; Rezende, Caroline Patini; Pessoni, André Moreira; Fernandes, Fabrício Freitas; Silva-Rocha, Rafael; Martinez, Roberto; Rodrigues, Marcio; Roque-Barreira, Maria Cristina; Casadevall, Arturo
Abstract Cryptococcus neoformans is an encapsulated fungal pathogen that causes cryptococcosis, which is a major opportunistic infection in immunosuppressed individuals. Mammalian β-galactoside-binding protein Galectin-3 (Gal-3) modulates the host innate and adaptive immunity, and plays significant roles during microbial infections including some fungal diseases. Here we show that this protein plays a role also inC .neoformans infection. We find augmented Gal-3 serum levels in human and experimental infections, as well as in spleen, lung, and brain tissues of infected mice. Gal-3-deficient mice are more susceptible to cryptococcosis than WT animals, as demonstrated by the higher fungal burden and lower animal survival. In vitro experiments show that Gal-3 inhibits fungal growth and exerts a direct lytic effect onC .neoformans extracellular vesicles (EVs). Our results indicate a direct role for Gal-3 in antifungal immunity whereby this molecule affects the outcome ofC .neoformans infection by inhibiting fungal growth and reducing EV stability, which in turn could benefit the host. The protein Galectin-3 modulates host immunity and plays roles during infections. Here, Almeida et al. show that this protein contributes to host defence against infection with the fungal pathogenCryptococcus neoformans by inhibiting fungal growth and inducing lysis of fungal extracellular vesicles.